Analisa Pasal 185 Kompilasi Hukum Islam Tentang Ahli Waris Pengganti - Haeratun - (Fakultas Hukum Universitas Mataram, 2016)
In the development of Islamic inheritance law. There is amatter concerning substitute heirs having the purpose of searching for justice for the theirs. Basically, the substitute heirs become heirs because the parents having the inheritance rights have passed away before the inheritors. The concept of substitute heirs under section 185 Compilation of Islamic Law that applies to all descendants of the heir who died first of the heirs and the heirs of the successor does not exceed an equal heir with being replaced. Beside that also, because the position of substitute heirs are not described in the Holy Koran it directly, but the content maslahah line with the objectives of Islamic Law that is to realize a sense of justice for the heirs. Because, the position of substitute heirsis not something contrary to maqashid al-Shari’ah, the benefit rational because the result of an ijtihad and considerations of justice upon the inheritance for heirs.